2011
DOI: 10.1093/neuonc/nor120
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive epidemiology of CNS tumors in France: results from the Gironde Registry for the period 2000-2007

Abstract: An increase in the incidence of CNS tumors has been observed in many countries in the last decades. The reality of this trend has been much debated, as it has happened during a period when computer-assisted tomography and MRI have dramatically improved the detection of these tumors. The Gironde CNS Tumor Registry provides here the first data on CNS tumor incidence and trends in France for all histological types, including benign and malignant tumors, for the period 2000-2007. Incidence rates were calculated gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
48
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 34 publications
6
48
0
3
Order By: Relevance
“…However, the incidence of primary brain tumors in the US (Dolecek et al, 2012), Korea (Lee et al, 2010) and France (Baldi et al, 2011) is more frequent in females. This might be due to the higher rate of meningiomas (30.6% and 35%) and lower rates for gliomas (17% and 30%) in Korea and US, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the incidence of primary brain tumors in the US (Dolecek et al, 2012), Korea (Lee et al, 2010) and France (Baldi et al, 2011) is more frequent in females. This might be due to the higher rate of meningiomas (30.6% and 35%) and lower rates for gliomas (17% and 30%) in Korea and US, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For the first time, a CNS tumor registry was begun in 1902 by Harvey Cushing (Wahl et al, 2009) and subsequently the registry expanded to other countries. The epidemiologic data from 1 1 , Rashid Ramezani 5 such registries has been published in the US, Canada, France, Denmark, Norway, Finland, Sweden, Australia, India, Korea and Japan (Davis et al, 1999;Kaneko et al, 2002;Bauchet et al, 2007;Pirouzmand and Sadanand, 2007;Deltour et al, 2009;Lee et al, 2010;Baldi et al, 2011;Dobes et al, 2011;Manoharan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Increase primarily in the elderly and females has also been observed in France (Baldi et al, 2011), while rise in childhoods rates was reported for Canada (Rosychuk et al, 2012). In contrast the situation appears stable for the Nordic countries (Schmidt et al, 2011) The situation is complicated by the vaious types of CNS tumours whcih have independent risk factors.…”
Section: Discussionmentioning
confidence: 98%
“…ous intracranial tissues [1] . Whatever be the histological type, studies concerning the etiology of brain tumors remain globally inconclusive.…”
mentioning
confidence: 99%
“…Other risk factors such as the use of pesticides, being exposed to electromagnetic fields, hormonal factors, infectious factors (such as herpes virus), smoking, alcohol consumption or diet have been hypothesized but without definitive conclusions [2,3,6] . A substantial increase in the incidence of these tumors has been observed in most countries in recent decades [1,7] , partially because of advanced diagnostic techniques, and also because of environmental and nutritional factors that may have a putative role [8] .…”
mentioning
confidence: 99%